Exercise books in the fascist era as a medium for ideological propaganda and an educational tool: the case of the Parini elementary school in Turin (1938-1942) - Morandini, Maria Cristina (Historia y Memoria de la Educación, 2019)
In recent historical-educational research, both in Italy and internationally, inquiry into the «material culture» of schools is seen as contributing crucially to the reconstruction of authentic everyday life in the classroom. The new sources used to document the specifics of educational experience include text books and exercise books. The library of Turin’s school museum conserves a «homemade» class library and a set of Italian language and handwriting exercise books, the work of fourth and fifth grade students at the local Parini elementary school from the years immediately preceding the fall of the fascist regime. An analysis of the pupils’ exercises in «good handwriting », essays, and summaries of Italian and international news events, brings to light the regime’s large-scale ideological propaganda efforts, which are reflected in the use of rhetorical language celebrating the figure of Il Duce and the fascist dictatorship with specific reference to aspects of its domestic and foreign policy and social-welfare and education programmes. The material examined also offers interesting insights into the educational activities conducted in the classroom: from study plans to curricular contents; from teaching methods and the treatment of errors to short and medium-term assessment criteria; from the formal testing of students’ educationalprogress to subjective perceptions of their current knowledge and personal potential for improvement.